THE MEDIATING ROLE OF CONSUMER SATISFACTION IN ENHANCING LOYALTY TOWARDS MALAYSIAN HALAL-CERTIFIED FOOD AND BEVERAGES - Madun, Azian; Kamarulzaman, Yusniza; Abdullah, Noorhidawati (Online Journal of Islamic Management and Finance (OJIMF), 2022)
The certification for halal food and beverage is issued by various organisations around the world. Nonetheless, the halal certification issued by the Malaysian government is often recognised as the most trustworthy and of the greatest quality. The purpose of this research is to look into the relationships between trust, customer expectations, religiosity, satisfaction, and loyalty, with a focus on the influence of satisfaction in increasing loyalty to halal-certified foods and beverages. A survey conducted among 399 Malaysian Muslims consumers shows that the highest correlation was between satisfaction and loyalty. Satisfaction was also the highest determinant for loyalty; while trustworthiness in the institution was the highest determinant in satisfaction. This study also found that satisfaction can increase loyalty. Findings of this study implies that the certifying institution should always increase and build their reputation among consumers, although the consumers may not necessarily understand the standards and process of certification. The findings also suggest that as long as consumers are satisfied with halal food and beverages, they will be more loyal to brands that carry Malaysian halal certification.